Physical, chemical, and optical data of SnS layers and light switching frequency dependent photoresponses - Patel, Malkeshkumar (Data Brief, 2017)
In this data article, vertically grown SnS layers were investigated. The growth processes of vertical SnS layers were discussed in our article [1]. This data article provides the chemical analysis using the XPS measurements for the SnS sample grown on a Si wafer. Deposition time varying SnS morphology changes were observed by FESEM. The cross-sectional images were achieved to monitor the SnS layer thickness. Refractive index of the grown SnS film was calculated using the reflectance data. A self-operating photoelectric was realized with structuring of SnS layers on the n-type Si wafer. Transient photoresponses were achieved by tuning the switching frequencies.